Pengaruh Motivasi Kerja terhadap Kinerja Pegawai Bidang Pendidikan Luar Biasa Pada Dinas Pendidikan Provinsi Jambi - Ubaidillah Ubaidillah; Masnun Masnun (Universitas Batanghari, 2022)
This study aims to obtain an overview of work motivation and employee performance at the Jambi provincial education office in the field of special education. Data collection was carried out through distributing questionnaires and carried out on 53 employees. The aspects studied are 5 dimensions of work motivation, namely physiological needs, security needs, love needs, self-esteem needs, and self-actualization needs. As well as the performance aspects studied include quantity, quality, punctuality, attendance, and ability to work together. Testing the data using statistical analysis such as validation and reliability tests, simple linear regression analysis, statistical hypothesis testing t test and coefficient of determination test from the results of the analysis with SPSS version 20 program, it can be seen that the regression equation formed The linear regression equation formed is Y 20.966+0.388X. The equation shows that the employee's performance is 0 then work motivation will increase by 0.388. From the results of the analysis obtained, it is known that the results of R square indicate that there is an influence of work motivation of 21.3% on employee performance, thus in the study of work motivation which has an influence on performance, the average number of effects of work motivation on employee performance as a whole is 21. ,3 and the remaining 78,7 are influenced by variables not examined in this study. Overall, from the 5 dimensions of work motivation variable, it has an average score of 221.8 which is categorized as good. Where the description of work motivation used by employees in the field of extraordinary education at the Jambi provincial education office is obtained, which is good for motivating work on the basis of consideration and good for work motivation. Motivation has a positive and significant influence on the performance of the Jambi provincial education office employees.